Metformin induced yellow nails: a rare entity - Sharma, Tarun; Sharma, Aradhna; Bhatnagar, Mukul (International Journal of Basic & Clinical Pharmacology, 2017)
This article reports an interesting and a rare case of metformin induced nail disorder in a middle aged female with type 2 diabetes. The patient had been receiving metformin one 1500mg daily from the last 6 months and noticed her finger nails gradually thickened and turned yellow. On stopping the metformin, the nails gradually normalized. The patient was treated further with glimepiride and insulin glargine. After 3 months of discontinuation of metformin there was a significant improvement in the nails. Clinicians should be aware of metformin induced yellow discolouration of nails, though a curable and reversible condition if diagnosed well in time.